Exploring the causes of the high incidence of delayed graft function after kidney transplantation in Brazil: a multicenter study - Sandes-Freitas, Taina Veras de (2021)
This retrospective multicenter (n = 18) cohort study evaluated the incidence, risk factors, and the impact of delayed graft function (DGF) on 1-year kidney transplant (KT) outcomes. Of 3992 deceased donor KT performed in 2014-2015, the incidence of DGF was 54%, ranging from 29.9% to 87.7% among centers. Risk factors ((lower-bound-95%CI) OR (upper-bound-95%CI)) were male gender ((1.066)1.249(1.463)), diabetic kidney disease ((1.053)1.296(1.595)), time on dialysis ((1.005)1.007(1.009)), retransplantation ((1.035)1.397(1.885)), preformed anti-HLA antibodies ((1.011)1.383(1.892)), HLA mismatches ((1.006)1.066(1.130)), donor age ((1.011)1.017(1.023)), donor final serum creatinine (sCr) ((1.239)1.317(1.399)), cold ischemia time (CIT) ((1.031)1.043(1.056)), machine perfusion ((0.401)0.542(0.733)), and induction therapy with rabbit antithymocyte globulin (rATG) ((0.658)0.800(0.973)). Duration of DGF > 4 days was associated with inferior renal function and DGF > 14 days with the higher incidences of acute rejection, graft loss, and death. In conclusion, the incidence and duration of DGF were high and associated with inferior graft outcomes. While late referral and poor donor maintenance account for the high overall incidence of DGF, variability in donor and recipient selection, organ preservation method, and type of induction agent may account for the wide variation observed among transplant centers.